Taxation and Transaction Costs in a General Equilibrium Asset Economy - Frank Milne; Xing Jin (Queen's University, Department of Economics, 2006)
Most financial asset pricing models assume frictionless, competitive markets that imply the absence of arbitrage opportunities. Given the absence of arbitrage opportunities and complete asset markets, there exists a unique martingale measure that implies martingale pricing formulae and replicating asset portfolios. In incomplete markets, or markets with transaction costs, these results must be modified to admit non-unique measures and the possibility of imperfectly replicating portfolios. Similar difficulties arise in markets with taxation. Some theoretical research has argued that some taxation functions will imply arbitrage opportunities and the non-existence of a competitive asset economy. In this paper, we construct a multi-period, discrete time/state general equilibrium model of asset markets with transaction costs and taxes. The transaction cost technology and the tax system are quite general, so that we can include most discrete time/state models with transaction costs and taxation. We show that a competitive equilibrium exists. Our results require careful modeling of the government budget constraints to rule out tax arbitrage possibilities.
Keywords: D52; G38; G12; 330; Taxation; Transaction Costs; General Equilibrium; Asset Economy